Efek Melaleuca Cajuputi terhadap Gambaran Histopatologi Organ Paru Tikus yang Diinduksi Asap Rokok - Cantika Dwi; Hasna Dewi; Ahmad Syauqy; Fairuz; Rina Nofrienis (Mataram University, 2026)
Exposure to cigarette smoke can cause lung tissue damage through mechanisms of chronic inflammation and oxidative stress. Melaleuca cajuputi essential oil contains 1,8-cineole and flavonoids, which possess anti-inflammatory and antioxidant properties, thereby offering potential protective effects on lung tissue. This study aimed to analyze the effects of Melaleuca cajuputi essential oil on the histopathological features of the lungs in cigarette smoke-induced rats. This experimental study used 28 male Wistar rats divided into four groups: negative control, positive control (cigarette smoke exposure), treatment group 1 (cigarette smoke exposure + Melaleuca cajuputi aromatherapy at a dose of 0.5 mL), and treatment group 2 (cigarette smoke exposure + aromatherapy at a dose of 1 mL). The treatments were administered for 30 days, with exposure to two cigarettes per day and aromatherapy for 15 minutes daily. Histopathological parameters assessed included inflammatory cell infiltration and alveolar septal destruction. Data were analyzed using the Kruskal–Wallis test and Mann–Whitney test. The results showed that administration of Melaleuca cajuputi at a dose of 0.5 mL significantly reduced inflammatory cell infiltration scores and alveolar septal destruction compared to the positive control group. Administration of the 1 mL dose significantly reduced inflammatory cell infiltration; however, it did not show a significant difference in alveolar septal destruction compared to the positive control group.